PENGARUH FIRM SIZE, DEBT TO ASSET RATIO, DAN CURRENT RATIO TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Mawarni, Astri Mulat; Kholis, Nur (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to determine the effect of company size, debt to asset, and current ratio on profitability. Food and baverage companies listed on the IDX for the 2019-2021 period are the population of this study. The number of samples used were 19 companies using a purposive sampling technique. Data analysis using multiple linear regression analysis method. The results of this study indicate that partially firm size, debt to asset ratio have a significant effect on profitability. The current ratio variable has no significant effect on profitability. Simultaneously it shows that firm size, debt to asset ratio, and current ratio have a significant effect on profitability. Keywords : firm size, debt to asset ratio, current ratio, profitability